2011
DOI: 10.1007/s10549-011-1873-8
|View full text |Cite
|
Sign up to set email alerts
|

Topoisomerase 2A gene amplification in breast cancer. Critical evaluation of different FISH probes

Abstract: The HER2 amplicon on chromosome 17q is variable in size and occasionally includes Topoisomerase 2A (TOP2A) at 17q21-22. It has been suggested that TOP2 coamplification, not HER2 amplification on chromosome 17q11.2-12, is a useful predictive marker of response to anthracycline-based chemotherapy in breast cancer patients. Given the significant toxicities of anthracyclines, the detection methods of TOP2A gene amplifications have to be standardized. We determined TOP2A gene alterations using two different fluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Furthermore, a short DNA probe for TOP2A was used to avoid overlap with HER2. 21 This may in part account for the low number of TOP2A -amplified cases in this study compared with previous studies and may reflect the true frequency of this finding.…”
Section: Discussionmentioning
confidence: 50%
“…Furthermore, a short DNA probe for TOP2A was used to avoid overlap with HER2. 21 This may in part account for the low number of TOP2A -amplified cases in this study compared with previous studies and may reflect the true frequency of this finding.…”
Section: Discussionmentioning
confidence: 50%
“…Recently, Varga et al show that using three different commercial kits to detect TOP2A amplification by in situ hybridization discrepant results were found, suggesting that the difference rate of TOP2A amplification is due to the different length of the DNA probes hybridizing to the TOP2A (17q21-q22). They demonstrated that larger TOP2A DNA probe (as in DAKO pharm DX TM with 228 kb) most likely overlaps with the HER2 gene region resulting in overdetection [26]. This is not the case in our series where we used a smaller probe with 67 kb, which could also explain the lower incidence of co-amplification of HER-2.…”
Section: Discussionmentioning
confidence: 59%
“…However we have only 10 cases with HER2 amplification, and 5 of those showed TOP2A alterations. In fact the amplification rate of the TOP2A gene in HER2 amplified breast carcinoma has been reportedly with variations from 7 to 50% [26]. Regarding the biological characteristics of the tumors, it was found that TOP2A altered tumors were more aggressive in terms of nuclear grade, more frequently with HER2 amplification and inflammatory type.…”
Section: Discussionmentioning
confidence: 98%
“…Outcomes of results both at the level of evaluation of TOP2A as well as at the level of interpretation are extremely different [24][25][26][27][28][29][30][31][32][33]. If biology of breast carcinoma is similar around the world, then methods of TOP2A evaluation, criteria of interpretation and selection of patients are responsible for the differences [34][35][36][37][38][39][40][41]. We put emphasis on criteria of interpretation, and decided to create out own system of We found in our study that cases with positive TOP2A status measured by the IHC method for TOP2A protein presented a statistically significantly better response to therapy which included anthracyclines as one of the chemotherapeutics (AC program in our study) in neoadjuvant therapy measured by relapses (DFS).…”
Section: Discussionmentioning
confidence: 99%